2015
DOI: 10.1542/peds.2015-0498
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment in School-age Girls With a Family History of Breast Cancer

Abstract: OBJECTIVE Understanding how young girls respond to growing up with breast cancer family histories is critical given expansion of genetic testing and breast cancer messaging. We examined the impact of breast cancer family history on psychosocial adjustment and health behaviors among >800 girls in the multicenter LEGACY Girls Study. METHODS Girls aged 6 to 13 years with a family history of breast cancer or familial BRCA1/2 mutation (BCFH+), peers without a family history (BCFH−), and their biological mothers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Research has revealed that most adolescent girls growing up in breast cancer families are aware of their risk for breast cancer in adulthood and there are things that they can do at their age to prevent cancer. 9 Thus, as many health and risk behaviors begin (eg, tobacco and alcohol intake, sexual activity, oral contraceptive use) or become established (eg, diet, exercise) in adolescence early communication about risk for adult cancer has the opportunity to provide a teachable moment. 10 Health and risk behaviors in preadolescence relate to the adoption and maintenance of health and risk behaviors throughout life.…”
mentioning
confidence: 99%
“…Research has revealed that most adolescent girls growing up in breast cancer families are aware of their risk for breast cancer in adulthood and there are things that they can do at their age to prevent cancer. 9 Thus, as many health and risk behaviors begin (eg, tobacco and alcohol intake, sexual activity, oral contraceptive use) or become established (eg, diet, exercise) in adolescence early communication about risk for adult cancer has the opportunity to provide a teachable moment. 10 Health and risk behaviors in preadolescence relate to the adoption and maintenance of health and risk behaviors throughout life.…”
mentioning
confidence: 99%
“…In an earlier study, BCFH-positive mothers and daughters reported greater breast cancer–specific distress compared with BCFH-negative mothers and daughters. 22 If replicated, it is plausible that early-life stress associated with a mother diagnosed with breast cancer may activate the HPA axis prematurely, thereby producing DHEA-S, which would explain our finding that breast cancer–specific distress was specific to DHEA-S and not the other androgens. Dehydroepiandrosterone sulfate is metabolized into androstenedione and testosterone; when puberty begins, the hypothalamic-pituitary-ovarian axis is activated and the ovary starts to contribute 25% to 50% of androstenedione and testosterone in circulation.…”
Section: Discussionmentioning
confidence: 77%
“…Such anxiety can be relieved by better communication, not by keeping secrets. 16,17 The medical team should thus discuss with the mother options for evaluating Karen’s mental state either in-person, by a pediatrician-mental health professional, or through a consultation with Karen’s primary pediatrician and treating psychologist, without her presence. Such a consultation might alleviate the mother’s concerns and persuade her to rethink her preferred approach to testing Karen.…”
Section: The Casementioning
confidence: 99%